A pilot observational study of recreational trail riding for Veterans with addictive disorders - Karl H. Hoopes; Makenna Osborne; William R. Marchand; Katryna Joubert; Elena Nazarenko; Heather Black; William Klinger; Stephen Sheppard (Elsevier, 2022)
Objectives: The aim of study was to assess the safety, feasibility, and preliminary outcomes of recreational trail riding for Veterans with addictive disorders. Design: This was an observational pilot study. Setting: United States Veterans Health Care Administration Medical Center. Participants were 18 Veterans, 13 males and 5 females All had at least one addictive disorder, with most common being alcohol use disorder. Intervention: A recreational trail ride of approximately two hours duration. Main outcome measures: Assessment of safety and pre- and post-intervention instruments, The State-Trait Anxiety Inventory, Craving Experience Questionnaire, Positive and Negative Affect Scale and Conner-Davidson Resilience Scale were utilized to assess changes in anxiety, craving, affect, and resilience, respectively. Results: The intervention was feasible to utilize for the population studied. In addition, it was possible to conduct the rides in such a way as to minimize risk to participants and there were no serious adverse outcomes to patients, staff, or equines. However, there was one incident that had potential to cause injury. There were significant pre- to post-intervention decreases in anxiety, negative affect and craving as well as increased positive affect. There was not a statistically significant increase in resilience. Conclusions: These results indicate that recreational trail riding is, at least in some settings, feasible to utilize for this population. The safety assessment indicated that this intervention can be conducted in a manner such that risk can be mitigated. However, trail riding is a dangerous activity that can result in serious injury or death to participants. Thus, such activities should only be considered by programs that have the ability to implement stringent safety protocols. Preliminary outcomes suggest that this intervention has the potential to be beneficial to for Veterans with addictive disorders. Additional, more rigorous randomized, controlled studies are warranted.